STATE POLICY FOR THE FORMATION OF HISTORICAL MEMORY OF THE GREAT PATRIOTIC WAR 1941–1945: REGIONAL EXPERIENCE - A. I. TETUEV (Кавказология, 2021)
The article examines the legal framework of patriotic education of citizens of the Russian Federation and the experience of forming historical memory of the Great Patriotic War of        1941–1945 on the example of Kabardino-Balkaria. The state policy of patriotic education of citizens is analyzed in the context of changes in foreign policy and socio-political life in modern Russia. The process of development of regional legislation on the management of the sphere of patriotic education of citizens is considered. The experience of the work of state authorities, educational organizations and institutions of civil society in Kabardino-Balkaria in organizing the military-patriotic education of youth is summarized. The article reveals the activities of search teams to perpetuate the memory of those who died during the Great Patriotic War, as well as secondary schools, museums and libraries to form civic values of youth. The problems in the system of organization of patriotic education are revealed.